STUDY OF ENDOTHELIAL INFLAMMATION IN PATIENTS WITH GOUT - Nigora T. Akramova; Dildora A. Nabiyeva; Turdikul A. Bobomurodov; Dilnoza T. Bobomurodova (Central Asian Journal of Medicine, 2025)
Background: Gout is a chronic inflammatory disease associated with hyperuricemia and systemic endothelial dysfunction. Recent studies have highlighted the role of endothelial and platelet activation in the development of vascular complications in gout. Objective: To investigate endothelial inflammation in patients with gout by evaluating plasma P-selectin levels as a biomarker of endothelial and platelet activation. Methods: A total of 65 patients with gout and 20 healthy controls were enrolled. Plasma P-selectin levels were measured using ELISA. Statistical analysis was performed using Student’s t-test. Results: Plasma P-selectin levels were significantly elevated in gout patients (mean 0.79 ± 0.63 ng/mL) compared to the control group (mean 0.08 ± 0.04 ng/mL, p < 0.001). Elevated levels were found in 58,4 % of patients, indicating widespread endothelial and/or platelet activation. Conclusions: P-selectin may serve as a reliable biomarker for endothelial inflammation and thrombotic risk in gout. These findings support its potential role in disease monitoring and highlight the need for further research to explore its prognostic value.